2019
DOI: 10.1002/pen.25084
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electrical, mechanical, and thermal properties of functionalized multiwalled carbon nanotubes‐reduced graphene Oxide/PMMA hybrid nanocomposites

Abstract: Electrical, mechanical, and thermal properties of the poly(methyl methacrylate) (PMMA) composites containing functionalized multiwalled carbon nanotubes (f‐MWCNTs) and reduced graphene oxide (rGO) hybrid nanofillers have been investigated. The observed electrical percolation threshold of FHC is 0.8 wt% with maximum conductivity of 1.21 × 10−3 S/cm at 4 wt% of f‐MWCNTs. The electrical transport mechanism and magneto resistance studied of hybrid composites have also been investigated. Progressive addition of f‐M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…For instance, PI/SiCNW-GS hybrids, where the PI matrix was prepared from PMDA and ODA using DMAc as an organic solvent, exhibited tensile strengths of 79.5–95.5 MPa, tensile moduli of 1608–2233 MPa, and elongations at break of 9.6–23.8% . Meanwhile, the tensile properties of the PI hybrids were much better than those of other polymer-based hybrid materials, such as TiO 2 /PS (tensile strength: 28.5–42 MPa, tensile modulus: 327–520 MPa, and elongation at break: 6.5–11%) and f-MWCNTs-rGO/PMMA (tensile strength: 21.2–28.9 MPa and tensile modulus: 1420–2130 MPa) . The high tensile properties of PI-based hybrids are surely due to the presence of aromatic groups in the main chain and strong intermolecular forces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, PI/SiCNW-GS hybrids, where the PI matrix was prepared from PMDA and ODA using DMAc as an organic solvent, exhibited tensile strengths of 79.5–95.5 MPa, tensile moduli of 1608–2233 MPa, and elongations at break of 9.6–23.8% . Meanwhile, the tensile properties of the PI hybrids were much better than those of other polymer-based hybrid materials, such as TiO 2 /PS (tensile strength: 28.5–42 MPa, tensile modulus: 327–520 MPa, and elongation at break: 6.5–11%) and f-MWCNTs-rGO/PMMA (tensile strength: 21.2–28.9 MPa and tensile modulus: 1420–2130 MPa) . The high tensile properties of PI-based hybrids are surely due to the presence of aromatic groups in the main chain and strong intermolecular forces.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, PI/ SiCNW-GS hybrids, where the PI matrix was prepared from PMDA and ODA using DMAc as an organic solvent, exhibited 57 Meanwhile, the tensile properties of the PI hybrids were much better than those of other polymer-based hybrid materials, such as TiO 2 /PS (tensile strength: 28.5−42 MPa, tensile modulus: 327−520 MPa, and elongation at break: 6.5− 11%) 58 and f-MWCNTs-rGO/PMMA (tensile strength: 21.2− 28.9 MPa and tensile modulus: 1420−2130 MPa). 59 The high tensile properties of PI-based hybrids are surely due to the presence of aromatic groups in the main chain and strong intermolecular forces. Therefore, the selection of PI (which has excellent comprehensive performance and is praised as a "problem solver") as the matrix material is very important for stability during further processing and the long-term application of hybrid materials.…”
mentioning
confidence: 99%
“…Thermal and antibacterial properties of nanocomposites of functionalized‐PMMA were successfully being demonstrated and highlighted the role of AgNPs and Nanoclay with the polymer matrix. [ 23 ] Recently new properties in the area of functionalization had been explored by Sa et al [ 24 ] who examined the effect of functionalized multiwalled carbon nanotubes‐reduced graphene oxide on electrical, mechanical, and thermal properties of PMMA nanocomposites and Hamza et al [ 25 ] who worked for optomechanical properties by investigating the effect of grafting polyamide‐6 fibers with PMMA on its intrinsic optical properties. Therefore by moving through variation literatures, it was found that the scientists were worked for the properties and applications of the functionalized nanocomposites but were inadequate to supply the information at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interfacial region between a polymer and a foreign substance has been actively studied. [ 1‐8 ] In evaluating polymeric materials, the glass transition temperature ( T g ) is considered one of the most important factors, particularly for amorphous polymers. In recent years, research on the T g for polymer thin films has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%